Uso de letras de samba-enredo como instrumento auxiliar ao ensino de história em turmas do 9° ano do ensino fundamental – uma possibilidade - Silva, Ricardo Oliveira da (2021)
The present work addresses the possibility of using samba-enredo lyrics as an auxiliary instrument for the teaching of History in classes of the 9th year of Elementary School. The choice of this theme is due to the subjective charm of the author of this production for the samba schools and, consequently, for the samba-plots that guide them in the parades. Although some works exist dealing with samba, carnival and history, the theme of running out is far. Here is the justification for this production, the variety of samba-enredo, which narrate the most diverse themes, certainly still yields a lot. Can this work contribute to the teaching of History, in particular, from the historical narratives. This mainly aims to demonstrate the use of sambaenredo lyrics as auxiliary tools for the teaching of History in elementary school of the final series, since it was the same developed in a school unit in the interior of the State of Bahia that exclusively attends to this modality of education. teaching. In addition, we sought to demonstrate and propose the use of these letters as part of the teaching methodology of History, through the elaboration of didactic sequences in which the BNCC and the proposal of the work are aligned. In this production of this work, not only bibliographic research was used, but also the experimentation of the proposal, affected, by the way, by the world pandemic. Even so, the belief in the possibility of using samba-plot lyrics in the teaching of History from the comparison of narratives, the work of the didactic sequences remains in the comparison between narratives.